Species List, Age and Sex Composition of Wild Animals Harvest in Bagale Hill of Girei Local Government Area of Adamawa State, Nigeria - Kwaga, B.T.; Thiliza, S.J.; Suleiman, .J. M.; Khobe, D. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
The study was undertaken to assess the check-list, age and sex composition of wild animals harvest in Bagale Hills of Girei Local Government Area of Adamawa State, Nigeria. Three locations (Girei 1, Jabbi-lamba and Labondo) were identified for the study. Rural appraisal techniques, literatures, visit to bush meat selling and processing centers as well as structured questionnaires were used to obtain data of the stated objectives. Simple descriptive statistics (frequency tables and and student t-test) were used in the analysis of data. Results obtained showed that majority of the respondents were males (66.67%) within the ages of 31 and above 50 years (23.08%), bush meat vendors (26.87%) and are indigenes (31.94%) of the area. The result indicated that most of the respondents preferred bush meat (61.43%) especially large mammals (66.67%) as source of protein in the study area. The result of check-list of wild animal species showed that 18 species of mammals, 6 species of reptiles and 9 species of birds were identified in the area. Results of age and sex composition of wild animal harvest showed that the number of adults harvested is significantly higher (P< 0.05) than the sub-adults and juveniles; while the number of females killed is significantly higher (P< 0.05) than that of males. To avoid the future extinction of the existing wild animal species, strict supervision of their harvest should be recommended by the authority concerned.